Fifteen-minute consultation: A practical approach to developmental regression in children. Issue 4 (4th September 2018) - Smith, Thomas; Ram, Dipak
Abstract : Developmental regression is an important red flag in any child's developmental performance and should be recognised promptly. It is the loss of previously acquired skills and can affect any sphere of childhood development. Presentation and underlying causes are heterogeneous in nature, in turn presenting many clinical challenges. While broad, the causes of regression can be categorised based on clinical findings, so that investigation and management options can be tailored appropriately. It is extremely important to try and make a definitive diagnosis if possible. This allows appropriate initiation of treatment for potentially reversible causes and for specific therapies, which may alter disease progression and improve quality of life in some cases. This article outlines a systematic approach to the evaluation of a child with suspected regression, covering the nature of presentation, key differential diagnoses, first-line investigations and management.